ANALISIS PERBEDAAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH EX-DEVIDEND DATE DI BURSA EFEK INDONESIA - Sri Yenti Naibaho, 10.05.52.0189; Parmono Hadi, Teguh (Students Journal of Accounting and Banking, 2014)
This research aims to analyze the difference between the stock price and trading volume activity on the ex-dividend date announcement in the Indonesian Stock Exchange, by taking a sample of 50 companies. The sample from this research was divided into two, they areincreasing dividend and decreasing dividend. Research period 20 days are divided into two periods of 10 days before and 10 days after the ex devident date. The methods used in this research is event study will that observe the price movement and trading volume activity in the capital market. The results indicate that at the significant level of 5%, there are 2 periods that still generates a significant share price difference on the increasing dividend, they are the 10th day and the 7th day after and before ex-devidend date. Whereas the increase devidend was not making a significant difference to the tranding volume activity, and the dividend decrease, stock price and tranding volume activity does not reveals a significant difference. The final conclusion is that stock price will negatively reacted to the announcement of increasing dividend at the ex-dividend date and positively reacted to the announcement of the decreasing dividend at the ex-dividend date. Keywords: Ex-Devidend Date, Stock Prices, Trading Volume Activity